Case report: Vedolizumab in Oral Crohn’s disease: the downsides of a gut-specific therapy for a multi-site disease - Harte, Molly; Macken, John; Zou, Lifong; Fortune, Farida (Frontiers in Medicine, 2024)
Introduction Crohn’s disease (CD) is a chronic inflammatory bowel disease which can affect any area of the gastrointestinal tract, including oral tissues. The complex nature of this disease demands interdisciplinary management, especially when both intestinal and oral manifestations are present. Case This report presents the case of a 28-year-old male patient with oral, ileo-caecal and peri-anal CD managed jointly between Gastroenterology and Oral Medicine. Treatment with vedolizumab, an α4β7 integrin with gut-selective anti-inflammatory activity, resulted in excellent ileo-caecal disease control, but was ineffective in controlling oral manifestations. The absence of MAdCAM-1 expression in oral tissues, necessary for vedolizumab’s mechanism, meant that the drug’s anti-inflammatory effects were limited to the gut. This limitation led to worsening oral symptoms, necessitating concomitant azathioprine therapy to manage oral inflammation. Conclusion Multidisciplinary collaboration is important when managing CD patients with both oral and gut involvement in CD. Clinicians should be aware that vedoluzimab may be beneficial for intestinal CD, but does not target inflammation in oral tissues due to its gut-specific action. Good knowledge of the pharmacology and mechanism of action of drugs prescribed can aid decision making when prescribing for this group of patients and can limit the need for polypharmacy, often associated with an increased adverse effect profile.